Could Lockdown Really Lockdown Covid-19 Spread: A Data-based Analysis in India - Saijan, Sanjo; Paul, Aby; Joby, Joel; Joseph, Jeeva; Sebastian, Stelvin; Vilapurathu, Jobin Kunjumon (Journal of Pharmacy Practice and Community Medicine)
Objective: To compare the impact of lockdown in Maharashtra, Kerala and United States. Methodology: We conducted a prospective observational study in order to assess and compare the impact of lockdown between Kerala, Maharashtra and United States (US). The study involved the collection of data from two phases. The first phase is the time from the index case reported in each country till the 14th day after the declaration of lockdown in that country. The second phase involved the data collected from the 15th day to the 28th day of lockdown. Data storage and analysis were performed using Microsoft excel and SPSS version 24. Result: As per 21st April, 426 cases were reported in Kerala among which 307 (70.07%) recovered, active cases were 117 and 2 deaths (0.4694%). Whereas in Maharashtra 7628 cases were reported and among which 1076 had recovered and there was 323 deaths. The total number of cases reported before lockdown in Maharashtra was 97 and in Kerala was 95. After the 29 days of lockdown the increase in the number of cases in Maharashtra was significantly higher when compared with Kerala. Also, the recovery rate before and after lockdown in Kerala was 4.10% and 72.53% respectively. In Maharashtra recovery rate before and after was 70.93% and 14.00% respectively. Conclusion: The implementation of lockdown had a great impact on reducing the transmission of infection across the country. The number of cases also reduced due to this lockdown, but its effectiveness varied from place to place.
Keywords: COVID-19 in India; Corona virus; Impact of lockdown; Viral infection; Pandemic; SARS- CoV-2